2013
DOI: 10.1590/s0100-204x2013000700003
|View full text |Cite
|
Sign up to set email alerts
|

Extratos etanólicos de manga como antioxidantes na alimentação de poedeiras

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de extratos etanólicos do caroço e da casca de manga, sobre o desempenho de poedeiras e sobre a qualidade e estabilidade lipídica dos ovos. Um total de 180 poedeiras comerciais Hisex White foi distribuído ao acaso em seis tratamentos, com cinco repetições de seis aves. Os tratamentos consistiram de: ração sem adição de antioxidante; ração com 200 ppm do antioxidante butilato de hidroxitolueno (BHT); ração com 200 ou 400 ppm de extrato da casca de manga (Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
(45 reference statements)
2
11
0
3
Order By: Relevance
“…In this study, there was an evident change in the feed intake, where the inclusion of fish by-product meal resulted initially in an increased intake, which, according to the aforementioned authors, is because products of animal origin directly affect the palatability of the food, and birds have a predilection for foods with medium to high lipid content (Freitas et al, 2013;Nogueira et al, 2014). Also in this context, a decrease in consumption was observed, which may be related to the energy needs of the birds caused again by the lipid content observed in the composition of fish by-product meal and its effect when included in larger quantity in the diets.…”
Section: Resultsmentioning
confidence: 64%
“…In this study, there was an evident change in the feed intake, where the inclusion of fish by-product meal resulted initially in an increased intake, which, according to the aforementioned authors, is because products of animal origin directly affect the palatability of the food, and birds have a predilection for foods with medium to high lipid content (Freitas et al, 2013;Nogueira et al, 2014). Also in this context, a decrease in consumption was observed, which may be related to the energy needs of the birds caused again by the lipid content observed in the composition of fish by-product meal and its effect when included in larger quantity in the diets.…”
Section: Resultsmentioning
confidence: 64%
“…The guava extract ellagic acid was ineffective to improve the egg quality. Freitas et al (2013) confirmed that the use of synthetic antioxidant or ethanolic mango extracts do not affect the breeder's performance, but it improves the albumen quality and the lipid eggs stability. Oliveira et al (2018) verified that the use of copaiba and sucupira oils in the breeder's diet have a positive impact in the albumen quality and the yolk's pH.…”
Section: -Coefficient Of Variationmentioning
confidence: 54%
“…Resultados similares, foram relatados por Rizzo et al (2010), que utilizaram misturas de extratos vegetais em dietas para frangos de corte, inclusive os testados nesta pesquisa, e relataram que estes não influenciaram as variáveis de desempenho. Do mesmo modo, Freitas et al (2013) trabalhando com extratos de mangas para poedeiras comerciais com 40 semanas de idade, observaram que não houve diferença significativa no consumo de ração das aves e consequentemente o desempenho não foi afetado.…”
Section: Resultsunclassified